The increasing of fibroblast growth factor 2, osteocalcin, and osteoblast due to the induction of the combination of Aloe vera and 2% xenograft concelous bovine - Utari Kresnoadi (Dental Journal (Majalah Kedokteran Gigi), 2012)
Background: To make a successfull denture prominent ridge is needed, preservation on tooth extraction socket is needed in order to prevent alveol bone resorption caused by revocation trauma. An innovative modification of the material empirically suspected to be able reduce inflammation caused by the revocation trauma is a combination of Aloe vera and xenograft concelous bovine (XCB) and Aloe vera is a biogenic stimulator and accelerating the growth of alveolar ridge bone after tooth extraction. Purpose: The research was aimed to determine of the increasing alveol bone formation by inducing the combination of Aloe vera and 2% xenograft concelous bovine. Methods: To address the problems, the combination of Aloe vera and xenograft concelous bovine was induced into the tooth extraction sockets of Cavia cabayas which devided on 8 groups. Groups control, filled with XCB, Aloe vera and Aloe vera and XCB combination, at 7 days and 30 days after extraction. Afterwards, immunohistochemical examination was conducted to examine the expressions of FGF-2 and osteocalcin, as the product of the growth of osteoblasts. Results: There were significantly increases expression of FGF-2 and osteocalcyn on group which filled with XCB, Aloe vera and combined Aloe vera and XCB. Conclusion: It may be concluded that the induction of the combination of Aloe vera and xenograft concelous bovine into the tooth sockets can enhance the growth expressions of FGF-2 and osteocalcin as the product of osteoblasts, thus, the growth of alveolar bone was increased.Latar belakang: Untuk keberhasilan pembuatan gigitiruan diperlukan ridge yang prominent, maka diperlukan suatu preservasi soket pencabutan gigi untuk mencegah terjadinya resopsi tulang alveolar akibat trauma pencabutan. Suatu inovasi modifikasi bahan yang diduga secara empiris dapat mengurangi keradangan karena trauma pencabutan adalah berupa kombinasi Aloe vera dan xenograft concelous bovine (XCB). Aloe vera yang merupakan biogenik stimulator untuk merangsang dan mempercepat pertumbuhan tulang alveolar setelah pencabutan gigi. Tujuan: untuk membuktikan bahwa induksi kombinasi Aloe vera dan xenograft concelous bovine 2% pada soket pencabutan gigi, dapat meningkatkan pembentukan tulang alveolar. Metode: Pengisian kombinasi Aloe vera dan XCB pada soket pencabutan gigi Cavia cabaya yang dibagi dalam 8 kelompok. Kelompok: kontrol, Aloe vera, XCB, kombinasi Aloe vera dan XCB, masing-masing dalam pemeriksaan 7 dan 30 hari. Kemudian dilakukan pemeriksaan imunohistokimia ekspresi FGF-2 dan osteocalcyn sebagai produk pertumbuhan sel osteoblas. Hasil: Terdapat peningkatan ekspresi FGF-2 dan osteocalcyn pada kelompok yang diisi XCB, Aloe vera dan kombinasi Aloe vera + XCB dibanding dengan kelompok kontrol. Kesimpulan: Induksi kombinasi Aloe vera dan xenograft concelous bovine 2% pada soket pencabutan gigi dapat, meningkatkan ekspresi FGF-2 dan osteocalcyn, sehingga dapat meningkatkan pertumbuhan tulang alveol.